Angiogenic biomaterials for diabetic wound healing: A review - Asad Ullah (4524541) (2025)
Diabetic wounds are a serious healthcare challenge, often lead to chronic ulcers, infections, and a high risk of amputation. Angiogenesis, the formation of new blood vessels, is crucial for supplying nutrients, oxygen, and growth factors necessary for effective wound healing. In diabetic wounds, impaired angiogenesis hinders the healing process, resulting in delayed tissue regeneration and prolonged wound closure. To induce angiogenesis, therapeutics like growth factors, cytokines, nitric oxide donors, and stem cells etc. have been utilized in wound healing but often face limitations such as rapid degradation, short half-life, and poor localized delivery, leading to reduced effectiveness. Biomaterials address these challenges by providing a controlled release platform that enhances the stability, bioavailability, and retention of these agents, ensuring prolonged therapeutic effects as well as creating a supportive environment for optimal angiogenesis. Therefore, this review explores the potential of biomaterials in addressing a major clinical challenge associated with diabetic wound healing. This review provides a comprehensive overview of current angiogenic therapeutics used to stimulate blood vessel formation in impaired tissues. It then explores biomaterial-based strategies engineered to enhance and sustain angiogenesis in diabetic wound environments. Finally, it discusses the key challenges associated with these approaches and outlines future prospects for developing more effective and clinical translatable treatments. Other Information Published in: Materials Today Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.mtcomm.2025.114508